A Statistical analysis study on MK Screens, Inc. - Dagondon, Elmer; Dato, Czarina T.; Velasquez, Kathering May G. (Diliman, Quezon City College of Engineering, 2001)
A study on statistical analysis was conducted on MK Screens, Inc. MK Screens is a company engaged in the production of well screens, gabbions and mattresses, SRC panels, welded wire mesh, pre-cast wall system and guard rail. The objective of the study deals with the application of the techniques learned in the statistical course. It also deals with relating the course to the manufacturing industry, specifically the industry of the mentioned product. Among the mentioned products, the group has limited the study and analysis on one of the main product of the company, which is the continuous slot water well screens. The group chose the mentioned product since it has the highest percentage of rework and since it accounts for the second largest product share among all the product of MK Screens. Continuous slot water well screens are filterind devices that allow water from aquifers to enterl the well while at the same time keeping majority of sand and gravel out of the pump. The group was able to identify the main problem of the company, which is the variation in the slot size causing the reworks of the product. The group was also able to pinpoint the two possible factors that greatly affect the variation in the slot opening, which are the spot-weld machine and the raw materials. The "Two Factor Factorial Design of Experiment" was used by the group to be able to identify which of the mentioned products are statistically significant. The group made the assumptions of the normality of data, independence of observations and equality of variance and proceeded with the Design of Experiment. Using the mentioned Design of Experiment, the group found out that the factor spot-weld machine is statistically significant. Based on the results of the statistical analysis, the group was able to conclude the design of the experiments is helpful tools to determine the significance of certain factors. In this case, the group concluded that the factor spot-weld machines are statistically significant. Also, based on the conclusion of the group, recommendations for the company were formulated. One of the recommendations of the group was the checking of the lubrication process of the spot-weld machine. Another recommendation of the group was the proper definition of the specifications of the machine set-up so that the set-up of the machine will not be dependent on the judgement or the skill of the operator. The group also recommends that the company conduct a further study on the mentioned factors.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: M.K. Screens incorporated; Screen process printing industry; Statistics